The association between healthy eating index score with semen parameters in infertile men: A cross-sectional study - Kimia Leilami; Azadeh Zareie; Mehran Nouri; Milad Bagheri; Mahsa Shirani (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Infertility has been a major problem for young couples in recent years. One way to assay the diet quality is the healthy eating index (HEI), related to infertility. Objective: This study aims to assess the association between the HEI score with semen parameters in Iranian infertile men. Materials and Methods: Two hundred and sixty eligible men (18-55 yr), were referred to the major infertility clinic in the summer of 2018 and entered this cross-sectional study. Based on the 5 th edition of the world health organization laboratory manual, semen parameters including sperm concentration, volume, motility, and morphology were analyzed, and to specify the dietary intake of individuals a 168-item questionnaire was used. Also, to calculate the total HEI score, all 13 components based on HEI-2015 components and scoring standards were summed up. Results: Participants in the highest tertile, had no difference in mean sperm parameters with those in the lowest tertile in the crude model. No significant association was found between sperm parameters and HEI score tertiles in the crude model, even after adjustment for potential confounders, except for concentration (OR: 0.39 and CI: 0.15, 0.99, p = 0.04). Participants in the highest tertile had a lower risk of abnormal concentration and motility in the crude model. The risk of abnormal concentration decreased, and motility increased in the adjusted model. Conclusion: In this cross-sectional study, there was no significant relationship between HEI and sperm indexes, except for sperm concentration. Therefore, more studies need to be done in the future.